1) [tex]\frac{x^{2}+2+3}{x} - \frac{6x}{x^{2}+2x+3}=5[/tex]
2) Задана функция f(x) = [tex]\frac{x}{\sqrt{x^{2}+3}}[/tex] Найдите f ' (1)
1)замена переменной (x^2+2x+3)/x =t, тогда t - (6/t)=5, после упрощения t^2-5t-6=0,
t=6; -1. Обратная замена: a) (x^2+2x+3)/x=6, после упрощения x^2-4x+3=0, x=1; 3
б) (x^2+2x+3)/x=-1, после упрощения x^2+3x+3=0, D<0 - решения нет
Ответ: {1; 3}
2) f '(x)=( x*(x^2+3)^(-1/2)) ' = (x^2+3)^(-1/2) - (1/2)*x*((x^2+3)^(-3/2))*2x=
=1/(x^2+3)^(1/2) - x^2/(x^2+3)^(3/2) = (x^2+3-x^2)/(x^2+3)*sqrt(x^2+3)=
=3/(x^2+3)*sqrt(x^2+3); f ' (1) = 3/(4*2)=3/8=0,375
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
1)замена переменной (x^2+2x+3)/x =t, тогда t - (6/t)=5, после упрощения t^2-5t-6=0,
t=6; -1. Обратная замена: a) (x^2+2x+3)/x=6, после упрощения x^2-4x+3=0, x=1; 3
б) (x^2+2x+3)/x=-1, после упрощения x^2+3x+3=0, D<0 - решения нет
Ответ: {1; 3}
2) f '(x)=( x*(x^2+3)^(-1/2)) ' = (x^2+3)^(-1/2) - (1/2)*x*((x^2+3)^(-3/2))*2x=
=1/(x^2+3)^(1/2) - x^2/(x^2+3)^(3/2) = (x^2+3-x^2)/(x^2+3)*sqrt(x^2+3)=
=3/(x^2+3)*sqrt(x^2+3); f ' (1) = 3/(4*2)=3/8=0,375